Multiple Cardiac Rhabdomyomas, Wolff-Parkinson-White Syndrome, and Tuberous Sclerosis: An Infrequent Combination - Elena Castilla Cabanes; Isaac Lacambra Blasco (Case Reports in Pediatrics)
Cardiac rhabdomyomas are benign cardiac tumours and are often associated with tuberous sclerosis. They are often asymptomatic with spontaneus regresion but can cause heart failure, arrhythmias, and obstruction. There have also been a few isolated reports of Wolff-Parkinson-White syndrome occurring in association with tuberous sclerosis and the great majority has been detected in patients with concomitant rhabdomyomas. We report a 12-day-old infant girl with tuberous sclerosis who presented with intraparietal and intracavitary rhabdomyomas with a Wolff-Parkinson-White syndrome (WPW). She represents one of the few published cases of WPW syndrome and tuberous sclerosis and particularly interesting because of intramural rhabdomyomas regression with persistent intracavitary rhabdomyomas after two years of followup.